Short Communication: Photogrammetric analysis of the number and pattern of dorsal cranium scale of juvenile green iguana (Iguana iguana) - BAGUS FAUZUL RAMADHANI; M. GANDUL ATIK YULIANI; GRACIA ANGELINA HENDARTI; TANTRI DYAH WHIDI PALUPI; ZULFI NUR AMRINA ROSYADA; SOEHARSONO SOEHARSONO; EPY MUHAMMAD LUQMAN; PUDJI SRIANTO; YENI DHAMAYANTI; BOEDI SETIAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Ramadhani BF, Yuliani MGA, Hendarti GA, Palupi TDW, Rosyada ZNA, Soeharsono, Luqman EM, Srianto P, Dhamayanti Y, Setiawan B. 2024. Short Communication: Photogrammetric analysis of the number and pattern of dorsal cranium scale of juvenile green iguana (Iguana iguana). Biodiversitas 25: 264-268. Pet animals can significantly positively impact mental health and reduce feelings of loneliness. Due to the large number of pets under care, there is a need for an efficient and effective method of pet identification. Thus, this study aims to identify changes in the dorsal cranium scale of juvenile green iguana (Iguana iguana (Linnaeus, 1758)) less than one year old. Dorsal cranium scales of juvenile green iguanas identified the number and pattern. Photo identification was examined for 18 green iguanas four times from the Faculty of Veterinary Medicine, Universitas Airlangga, Indonesia, at 12 weeks old, 14 weeks old, 16 weeks old, and 18 weeks old. The photo was taken on a studio set, focusing on the cranium of the green iguana to get the scale pattern correctly. Photo identification was taken to find scale number and pattern determinants by analyzing the app I3S. We collated and analyzed the weekly data to test hypotheses using repeated measure ANOVA analysis in IBM SPSS 23. The data showed that the number of scales of the dorsal cranium was stable during the four photos taken, and each individual could be the same in the number of scales. The pattern of dorsal cranium scales has a stagnant pattern for each individual, and each individual is different at scale patterns, so photo identification as individual identification is possible. However, it is not possible to use it to identify the age of the iguana.